2015
DOI: 10.1620/tjem.236.115
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Problems among Undergraduates in Fukushima, Tokyo, and Kyoto after the March 11 Tohoku Earthquake

Abstract: On March 11, 2011, the Great East Japan Earthquake devastated the Tohoku region, which led to a tsunami and a nuclear disaster. While these three disasters caused tremendous physical damage, their psychological impact remains unclear. The present study evaluated traumatic responses, internalizing (i.e., anxiety and depression), and externalizing (i.e., anger) symptoms among Japanese young people in the immediate aftermath and 2.5 years later. A total of 435 undergraduates were recruited from universities in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…According to these investigations, the most vulnerable group for the psychological impact of the disaster corresponds to young people from developing countries. There is much evidence that many adolescents who experience a natural catastrophe develop symptoms of posttraumatic stress [6], depressive disorders [7] and anxiety [8].…”
Section: Introductionmentioning
confidence: 99%
“…According to these investigations, the most vulnerable group for the psychological impact of the disaster corresponds to young people from developing countries. There is much evidence that many adolescents who experience a natural catastrophe develop symptoms of posttraumatic stress [6], depressive disorders [7] and anxiety [8].…”
Section: Introductionmentioning
confidence: 99%
“…Certain vulnerable populations have been identified in the aftermath of a nuclear disaster. Although research has shown impact on areas near and far to the disaster location [ 38 ], people living closest to the reactor are disproportionally affected by a nuclear disaster [ 22 , 24 ]. People who are forced to evacuate their homes due to a nuclear disaster have higher levels of distress [ 13 , 20 , 21 , 26 , 32 , 35 , 42 ].…”
Section: Protective Factors and Vulnerable Populationsmentioning
confidence: 99%
“…21 For non-FHMS studies (n = 46; 60.5%), a large number of the studies used convenience samples and focused on evacuees (living in and out of the Fukushima prefecture), children, and older adults. Other study populations focused on specific populations, such as hospital patients, 15,23,45,47,54,85,86 caregivers, 19,71 students, 16,30,33,42,[48][49][50]62 and workers of various occupations. Specifically, a series of studies were conducted among the NPP workers.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…40,46,78,89 Control groups were used in 13 studies (16.5%). 16,17,26,30,41,42,48,50,55,62,64,70,71 Most of the studies were based on responses from selfadministered questionnaires (68; 89.4%). Seven studies (9.2%) used medical records retrospectively for their data.…”
Section: Quality Assessmentmentioning
confidence: 99%